The Effect Of Investment Decisions, Funding Decisions, And Inflation Rate On Company Value In The Basic And Chemical Industry Sector Listed On The Indonesia Stock Exchange For The 2017-2021 Period - Andriyani, Ima; Zuliyana, Meti; Aryani, Dwi Septa; Agustina, Ekariani (Best Journal of Administration and Management, 2023)
This study seeks to ascertain the effects of funding choices, investment decisions, and inflation rates on firm value in manufacturing firms in the basic and chemical industries listed on the Indonesia Stock Exchange. In this study, a purposive sample of 10 basic industrial and chemical manufacturing firms was used. With the aid of SPSS 25.0 software for Windows, the analysis used in this study included descriptive statistical analysis, linearity testing, normality testing, classical assumption testing, multiple linear regression analysis testing, correlation coefficient testing, determination (), and hypothesis testing. In contrast to funding decisions, which are shown to have a considerable impact on firm value by independent variables, the results reveal that investment decisions and inflation rates have no significant impact on firm value. Simultaneously investment decisions, funding decisions, and inflation rates have a significant effect on firm value in the basic and chemical industry sectors listed on the IDX.